Changing Notions of Kinship and Family in Contemporary Urban Africa - Adepoju, Aderanti; Olajide, Oyeronke (Mahogany Journal De Social, 2025)
This study investigates the changing nature of kinship and family structures in urban Africa, focusing on the influence of urbanization, migration, and globalization on traditional family arrangements. The research aims to explore how these factors contribute to the redefinition of family and kinship in urban African settings. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews across four major African cities: Lagos, Nairobi, Johannesburg, and Accra. The results reveal a shift from traditional extended family systems to more nuclear family structures, with non-biological kin increasingly recognized as integral to family life. Migration plays a significant role in this transformation, as individuals maintain kinship bonds through remittances and digital communication despite geographical separation. Gender roles within the family also show signs of transformation, with men becoming more involved in caregiving and domestic duties in urban areas. These findings contribute to the understanding of kinship in urban Africa, emphasizing the flexibility and adaptability of family structures in response to modern socio-economic pressures. The study calls for policies that recognize the diversity of family forms and promote gender equality in caregiving roles. Further research is needed to explore the long-term socio-economic effects of these changes, particularly regarding migration and non-biological kin.